Issues and challenges of a liveable and creative city: the case of Penang, Malaysia - Christina Oon, Khar Ee; Khoo, Suet Leng (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
‘Liveable City’ is an urban planning concept that has recently attracted much attention. In Penang, the city-state has undergone massive social and economic developments. Penang’s popularity has increased following its capital city, George Town’s inscription into the UNESCO’s World Heritage List in 2008. In February 2013, Penang was also ranked as the 4th greatest place to retire abroad. In Asia, it was ranked the eighth most liveable city for two consecutive years by ECA (Employment Conditions Abroad) International. Although bestowed with these accolades, the actualization of sustained liveability in Penang is still a matter of serious concern amongst political leaders and Penangites themselves. This paper aims to explore and understand the issues and challenges besetting Penang in becoming a full-fledged liveable and creative city. The challenges and issues highlighted in this paper were gathered from several sessions of in-depth interviews with key informants. In sum, chronic traffic jam, lack of affordable housing, safety issues and scarcity of land were some of the critical issues highlighted.